2023
DOI: 10.1002/nop2.2054
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the ‘Jefferson Scale of Empathy’ in a sample of nursing students in the United Kingdom

Juping Yu,
Siva Ganesh,
Deborah Lancastle

Abstract: AimTo examine the psychometric properties of the ‘Jefferson Scale of Empathy’.DesignA methodological study was conducted.MethodsA sample of 230 nursing students was used to analyse the psychometric properties of the ‘Jefferson Scale of Empathy’. Exploratory and confirmatory factor analysis was used to test construct validity. Cronbach's alpha and item‐total correlations were carried out to test internal consistency reliability.ResultsThe mean score of the empathy SUM was 112.0 (SD: 12.6). A three‐factor model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(78 reference statements)
0
0
0
Order By: Relevance
“…The results of the study showed that the empathy score of nursing interns was 82.18 ± 15.55, which was lower than the findings of Li et al (24) and Yu et al (25). The reason for this analysis may be related to the difference in the study population, which were freshmen and sophomores, respectively, while the population of the present study was nursing students at the internship stage.…”
Section: Comparison With Literaturecontrasting
confidence: 81%
“…The results of the study showed that the empathy score of nursing interns was 82.18 ± 15.55, which was lower than the findings of Li et al (24) and Yu et al (25). The reason for this analysis may be related to the difference in the study population, which were freshmen and sophomores, respectively, while the population of the present study was nursing students at the internship stage.…”
Section: Comparison With Literaturecontrasting
confidence: 81%
“…The results of the study showed that the empathy score of nursing interns was 82.18 ± 15.55, which was lower than the findings of Li et al (24) and Yu et al (25). The reason for this analysis may be related to the difference in the study population, which were freshmen and sophomores, respectively, while the population of the present study was nursing students at the internship stage.…”
Section: Comparison With Literaturecontrasting
confidence: 81%